What did we learn from preparing for cross-border transmission of Ebola virus disease into a complex humanitarian setting - The Republic of South Sudan? - Olushayo Oluseun Olu; Richard Lako; Joseph Francis Wamala; Patrick Otim Ramadan; Caroline Ryan; Ifeanyi Udenweze; Kibebu Berta; Argata Guracha Guyo; Alex Sokemawu; Michael Tukuru; Henry John Gray; Alex Chimbaru (BMC, 2020)
Abstract Background Following the West Africa Ebola virus disease (EVD) outbreak (2013-2016), WHO developed a preparedness checklist for its member states. This checklist is currently being applied for the first time on a large and systematic scale to prepare for the cross border importation of the ongoing EVD outbreak in the Democratic Republic of Congo hence the need to document the lessons learnt from this experience. This is more pertinent considering the complex humanitarian context and weak health system under which some of the countries such as the Republic of South Sudan are implementing their EVD preparedness interventions. Main text We identified four main lessons from the ongoing EVD preparedness efforts in the Republic South Sudan. First, EVD preparedness is possible in complex humanitarian settings such as the Republic of South Sudan by using a longer-term health system strengthening approach. Second, the Republic of South Sudan is at risk of both domestic and cross border transmission of EVD and several other infectious disease outbreaks hence the need for an integrated and sustainable approach to outbreak preparedness in the country. Third, a phased and well-prioritized approach is required for EVD preparedness in complex humanitarian settings given the costs associated with preparedness and the difficulties in the accurate prediction of outbreaks in such settings. Fourth, EVD preparedness in complex humanitarian settings is a massive undertaking that requires effective and decentralized coordination. Conclusion Despite a very challenging context, the Republic of South Sudan made significant progress in its EVD preparedness drive demonstrating that it is possible to rapidly scale up preparedness efforts in complex humanitarian contexts if appropriate and context-specific approaches are used. Further research, systematic reviews and evaluation of the ongoing preparedness efforts are required to ensure comprehensive documentation and application of the lessons learnt for future EVD outbreak preparedness and response efforts.